Histamine Receptor H1–Mediated Sensitization of TRPV1 Mediates Visceral Hypersensitivity and Symptoms in Patients With Irritable Bowel Syndrome - Wouters, Mira M.; Balemans, Dafne; Van Wanrooy, Sander; Dooley, James; Cibert-Goton, Vincent; Alpizar, Yeranddy A.; Valdez-Morales, Eduardo E.; Nasser, Yasmin; Van Veldhoven, Paul P.; Vanbrabant, Winde; Van der Merwe, Schalk; Mols, Raf; et al. (Gastroenterology (New York, N.Y. 1943), 2016)
Histamine sensitizes the nociceptor transient reporter potential channel V1 (TRPV1) and has been shown to contribute to visceral hypersensitivity in animals. We investigated the role of TRPV1 in irritable bowel syndrome (IBS) and evaluated if an antagonist of histamine receptor H1 (HRH1) could reduce symptoms of patients in a randomized placebo-controlled trial. By using live calcium imaging, we compared activation of submucosal neurons by the TRPV1 agonist capsaicin in rectal biopsy specimens collected from 9 patients with IBS (ROME 3 criteria) and 15 healthy subjects. The sensitization of TRPV1 by histamine, its metabolite imidazole acetaldehyde, and supernatants from biopsy specimens was assessed by calcium imaging of mouse dorsal root ganglion neurons. We then performed a double-blind trial of patients with IBS (mean age, 31 y; range, 18–65 y; 34 female). After a 2-week run-in period, subjects were assigned randomly to groups given either the HRH1 antagonist ebastine (20 mg/day; n = 28) or placebo (n = 27) for 12 weeks. Rectal biopsy specimens were collected, barostat studies were performed, and symptoms were assessed (using the validated gastrointestinal symptom rating scale) before and after the 12-week period. Patients were followed up for an additional 2 weeks. Abdominal pain, symptom relief, and health-related quality of life were assessed on a weekly basis. The primary end point of the study was the effect of ebastine on the symptom score evoked by rectal distension. TRPV1 responses of submucosal neurons from patients with IBS were potentiated compared with those of healthy volunteers. Moreover, TRPV1 responses of submucosal neurons from healthy volunteers could be potentiated by their pre-incubation with histamine; this effect was blocked by the HRH1 antagonist pyrilamine. Supernatants from rectal biopsy specimens from patients with IBS, but not from the healthy volunteers, sensitized TRPV1 in mouse nociceptive dorsal root ganglion neurons via HRH1; this effect could be reproduced by histamine and imidazole acetaldehyde. Compared with subjects given placebo, those given ebastine had reduced visceral hypersensitivity, increased symptom relief (ebastine 46% vs placebo 13%; P = .024), and reduced abdominal pain scores (ebastine 39 ± 23 vs placebo 62 ± 22; P = .0004). In studies of rectal biopsy specimens from patients, we found that HRH1-mediated sensitization of TRPV1 is involved in IBS. Ebastine, an antagonist of HRH1, reduced visceral hypersensitivity, symptoms, and abdominal pain in patients with IBS. Inhibitors of this pathway might be developed as a new treatment approach for IBS. ClinicalTrials.gov no: NCT01144832.